Variability of the Hot Box Method in Assessing Thermal Resistance of a Double Leaf Brick Wall - Manuel Ribas; Eva Barreira; Ricardo M. S. F. Almeida (Infrastructures)
The accurate thermal performance assessment of building components is critical for improving energy efficiency in buildings, mainly as space climatization accounts for a large percentage of energy consumption. The literature review points out multiple parameters that influence the measurement of the U-value using the HFM method. However, most of these studies are focused on in situ tests and little information exists on the variability of the results of the hot box method to assess thermal resistance. According to EN 1934, a baffle must be positioned between the surface of the specimen and the fans of the climatic chamber to maintain acceptable air temperature gradients and uniform air temperature distribution to minimize the convective effects. However, no clear information about its position is given. This study investigates the variability in the measurement of the thermal resistance of double leaf brick wall specimen using the hot box method, focusing on the effect of the layout configuration. An experimental campaign was carried out and three configurations were considered: no baffle, a baffle positioned 1.15 m from the wall, and a baffle positioned 0.05 m from the specimen. The experimental results demonstrate that baffle positioning significantly influences measurement variability. The best-performing configuration (P1) resulted in the lowest variability and the closest agreement with theoretical values, with an average R-value deviation of approximately 25%. These findings are relevant for optimizing testing protocols and improving the reliability of thermal resistance assessments. Furthermore, the results have implications for energy efficiency policies and building retrofitting strategies, aligning with global sustainability goals to reduce building energy demand and carbon emissions.